Case Report: A Possible Case of Congenital Erythropoietic Porphyria in a Gir Calf: A Clinical, Pathological, and Molecular Approach - Queiroz, Cintia Regina Rêgo; Machado, Mizael; Bromberger, Cristiana Raach; Oliveira-Filho, Jose Paes; Borges, Alexandre Secorun; Soto-Blanco, Benito; Borges, José Renato Junqueira; Câmara, Antônio Carlos Lopes; Castro, Márcio Botelho de (Frontiers in Veterinary Science, 2021)
Congenital erythropoietic porphyria (CEP) is a rare hereditary autosomal recessive disease that has never been reported in Zebu cattle. A 3-day-old Gir calf showed discoloration of the teeth, fever, dehydration, and dyspnea. Pink teeth, red-brown periosteum and bone marrow, and a fluorescent bright-pink coloration of the bone marrow and articular surfaces under ultraviolet light were the main gross findings. Aggregates of periodic acid-Schiff (PAS) stained porphyrin pigments were evident in the lungs, kidneys, and liver. An intron 8 single nucleotide polymorphism (SNP) in both the Gir calf and control animals, along with the absence of the uroporphyrin III cosynthetase (UROS) gene mutation were observed. Most SNPs were located in the intron regions of the UROS gene, without relevance for CEP. A continuous loss of genetic variability and an increase in inbreeding in some herds may be related to CEP in Gir cattle, one of the most prominent Zebu breeds worldwide. In summary, this report describes a presumptive case of congenital erythropoietic porphyria in a Gir calf, based on clinical and pathological findings. Definitive diagnosis would require measurement of porphyrin levels in blood, urine or tissues or the identification of UROS gene defects.